Proses dan Bentuk Adaptasi Sosial Budaya Prajurit Tentara Perempuan (KOWAD) di Lembaga Kedinasan TNI AD (DISJASAD) - Resti Putri Sugiharti (Umbara, 2019)
The number of female soldiers (KOWAD) in Dinas Jasmani Angkatan Darat (Disjasad) are less than their counterparts. Thus, made female soldiers applying a unique approach of adjustment upon entering the male dominated environment. This research aims to describe the deep understanding of the patterns and procces of adjustment of female soldiers at Disjasad. Research methods used in this research is qualitative methods with an ethnography model.The result shows that masculine environment in Disjasad did not affect the female soldiers, due to the ask division which feminin chore such as in administration, medical and health divisions. Every female soldiers had applied unique way of adjusment and their patterns of adjustments are conformity and ritualism upon addressing regulation in army headquarters. The patterns of adjustment are influenced by internal factor which are personality, ability, character and external factor such as cultural gap, previous job as well as gender.